Atypical Cutaneous Lymphoid Hyperplasia of mixed B/T type in a 15-year-old girl. - Ricci, C.; Cavazza, A.; Di Lernia, V. (European Journal of Pediatric Dermatology, 2005)
Atypical Cutaneous Lymphoid Hyperplasia of mixed B/T type in a 15-year-old girl.